Exploring The Interplay of Multifaceted Factors: A Comprehensive Analysis of Risk Perception, Anxiety, and Age-Related Dynamics in The Post-Covid-19 Era - Hughey Surman, Stacy; Dadzie, Justice; Ezugwu, Ifesinachi Jude (Papanda Publisher, 2024)
This research delves into the intricate dynamics of risk awareness and anxiety among college undergraduates in the aftermath of the COVID-19 pandemic. It specifically examines the nuanced interplay between risk perception and anxiety levels, while also considering the impact of demographic factors such as gender, age, and religion on these psychological aspects. Conducted using a cross-sectional design involving 778 participants, the study employs regression analysis to unveil a significant positive association between perceived risk and risk perception, accounting for 56% of its variability. Furthermore, multivariate analysis of variance underscores the substantial overall effect of predictors on both risk perception and anxiety levels. Notably, age emerges as a significant influence on students' risk perception and anxiety levels. By shedding light on how college students perceive and cope with risks amidst the ongoing pandemic, this study offers valuable insights into the complex relationship between demographic variables and psychological responses. Ultimately, these findings can inform strategies aimed at supporting students during challenging times.